ANALYSIS OF COMPENSATION METHODS FOR ASTIGMATISM - Nascimento, Séverton de Vasconcelos; Trentin Sonoda, Rodrigo (Health and Society, 2023)
Visual compensation is essential to efective quality vision, in special astigmatic people. Dioptric lenses are a simple and effective option for compensation to moderate astigmatism, contact lenses offer greater freedom and comfort. Orthokeratology is a non-surgical technique that may be an option for those who wish to avoid refractive surgery or who are not eligible for it. It is important to carefully evaluate each visual compensation option and seek guidance from the optometrist to determine which is best for each case. This review demonstrate the methods and effectiveness of compensation for this ametropia and optometrist work.